Relative Consumption Concerns and the Optimal Tax Mix - Paul Eckerstorfer (Johannes Kepler University of Linz, Department of Economics, 2011)
This articles studies the optimal tax mix (taxes on income and commodities) under asymmetric information in a two-type model, when individuals make relative consumption comparisons. The model includes both positional and nonpositional goods, taking into account the fact that relative concerns matter for some but not for all commodities. We find that in general the whole tax system is affected by the externalities caused by the consumption of positional goods, notably also the taxes on income and on a non-positional good. The tax rates on positional goods are higher than in the absence of status effects, reflecting their Pigouvian role. The sign of the Pigouvian part in the income tax schedule is ambiguous and depends crucially on whether status goods are complements or substitutes to leisure.
Keywords: D62; H21; H23; 330; Optimal Taxation; Externalities; Relative Consumption; Einkommensteuer; Verbrauchsteuer; Optimale Besteuerung; Internalisierung externer Effekte; Asymmetrische Information; Konsuminterdependenz; Theorie